Pengaruh Self-Acceptance Terhadap Coping Strategy Orang Tua Dengan Anak Down Syndrome Di Yayasan Persatuan Orang Tua Down Syndrome (POTADS) - Pratiwi Jessy Saputri; Zirmansyah Zirmansyah (Observasi : Jurnal Publikasi Ilmu Psikologi, 2024)
Parents who have children with Down syndrome experience various dynamics and problems to be able to accept the circumstances that occur. Parents' self-acceptance is an important aspect in caring for, educating, and raising the baby. This study aims to determine the effect of self-acceptance on coping strategies of parents who have children with Down syndrome. Research using quantitative methods with a sample of 287 parents, who are members of the Down Syndrome Parents Association Foundation (POTADS). there are 46 statement items on the coping strategy scale (r = 0.873) and 16 items on the self-acceptance scale (r = 0.714) on a Likert model scale. The results of data analysis using simple linear regression tests show that there is a significant effect of self-acceptance on coping strategies with a sig value. <0.05. through the regression equation Ŷ= 77.608 + 1.090X. The correlation coefficient value is 0.489 and the coefficient of determination (R Square = 0.239). 23.9% self-acceptance influences the coping strategy of parents at the POTADS Foundation.